Import Competition and Gender Differences in Labor Reallocation - Hani Mansour; Pamela Medina; Andrea Velásquez (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study gender differences in the labor market reallocation of Peruvian workers in response to trade liberalization. The empirical strategy relies on variation in import competition across local labor markets based on their industrial composition before China entered the global market in 2001. In contrast to much of the existing literature, we find that import competition did not have persistent negative employment effects on men or led them to sort into the non-tradable or informal sectors. The adverse effects on the employment of low-educated women in the tradable sector, however, persist over time leading them to sort into the non-tradable sector or out of the labor force. The results are consistent with a mechanism in which gender occupational and industrial segregation leads to a widening of the gender gap in employment.
Keywords: E24; F14; J16; J71; 330; import competition; female employment; gender discrimination